Ghostly : a collection of ghost stories - Niffenegger, Audrey (Scribner, 2015)
"Collected and introduced by the bestselling author of The Time Traveler's Wife and Her Fearful Symmetry--including her own fabulous new illustrations for each piece, and a new story by Niffenegger--this is a unique and haunting anthology of some of the best ghost stories of all time. From Edgar Allan Poe to Kelly Link, M.R. James to Neil Gaiman, H. H. Munro to Audrey Niffenegger herself, Ghostly reveals the evolution of the ghost story genre with tales going back to the eighteenth century and into the modern era, ranging across styles from Gothic Horror to Victorian, with a particular bent toward stories about haunting--haunted children, animals, houses. Every story is introduced by Audrey Niffenegger, an acclaimed master of the craft, with some words on its background and why she chose to include it. Niffenegger's own story is, "A Secret Life With Cats." Perfect for the classic and contemporary ghost story aficionado, this is a delightful volume, beautifully illustrated. Ghostly showcases the best of the best in the field, including Edith Wharton, P.G. Wodehouse, A.S. Byatt, Ray Bradbury, and so many more"--